Effectiveness and safety of edoxaban in atrial fibrillation patients from the ETNA-AF global registry. (14th October 2021) - De Caterina, R; Wang, R; Shi, L; Pecen, L; Ye, X; Reimitz, P.-E; Chen, C; Unverdorben, M; Giugliano, R.P
Abstract: Background/Introduction: ETNA-AF (ETNA) is a multinational, prospective, observational study evaluating the experience with edoxaban in the clinical practice of patients with atrial fibrillation (AF). ENGAGE AF-TIMI 48 was a randomized double-blind trial that tested the clinical benefits of edoxaban versus warfarin. The recommended dose is 60 mg, dose-reduced to 30 mg daily in patients with at least 1 of 3 label-indicated criteria (renal impairment [creatinine clearance: 15–≤50 mL/min], weight ≤60 kg, or concomitant use of potent P-glycoprotein inhibitors). Purpose: We assessed whether the effectiveness and safety of edoxaban in clinical practice were consistent with findings from the pivotal randomized clinical trial. Methods: We obtained patient-level data from ETNA and ENGAGE AF-TIMI 48. We initially extracted patients from similar geographic regions, and then used propensity-score matching (PSM) to adjust key baseline characteristic differences between studies. The primary effectiveness endpoint was all stroke or systemic embolism (SSE) and mortality; the safety endpoint was major bleeding (MB). We used Cox proportional hazards models to compare event rates for the clinical outcomes between ETNA and ENGAGE AF-TIMI 48. Results: 8, 615 AF patients with CHADS2 score ≥2 received the 60 mg edoxaban recommended dose (5, 462 ETNA; 3, 153 ENGAGE AF-TIMI 48). After PSM, key baseline characteristics were well-balanced between the studies: mean age 71.0 years (SD: 9.07); for both ETNA and ENGAGE AF-TIMI 48 median CHA2DS2-VASc score and median HAS-BLED score were 4 and 2. The annualized incidence rate of SSE was 1.65% in ETNA vs 1.53% in ENGAGE AF-TIMI 48 (HR 0.98; 95% CI 0.49, 1.93; p=0.94). ETNA had similar annualized mortality, 2.81%, compared with ENGAGE AF-TIMI 48, 2.34%, (HR 1.49; 95% CI 0.84, 2.63; p=0.17). MB was less frequent in ETNA vs ENGAGE AF-TIMI 48 (1.10% vs 3.56%; HR 0.25; 95% CI 0.14, 0.44; p<0.05). Findings were similar for the recommended 30 mg edoxaban reduced dose. Conclusions: The effectiveness of edoxaban in clinical practice from a large registry was consistent with efficacy findings from the randomized controlled trial. We observed a lower rate of bleeding events in the ETNA observational study compared with the ENGAGE AF-TIMI 48 trial. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This study was sponsored by Daiichi Sankyo Inc.